Device Optimization and Large‐Scale Roll‐to‐Roll Manufacturability of Flexible Thin‐Film Thermoelectric Generators. Issue 9 (18th July 2021) - Tao, Xudong; Zhang, Kai; Gregory, Daniel; Liu, Junliang; Assender, Hazel E.
Abstract : The optimization of flexible thin‐film thermoelectric generators (TEGs) suitable for large‐area roll‐to‐roll (R2R) processing is investigated. The selection of suitable contact materials, in‐line patterning of connections, and dimension of the thermoelectric (TE) strip are studied. As a result, copper is selected for contacts because it possesses a similar performance to gold while being cheaper. Both in‐series‐ and in‐parallel‐connected devices are found to work well and provide a voltage‐dominant and current‐dominant power source, respectively. The Seebeck coefficient and internal resistance of a device are extracted from the fit line to the measured power data. The in‐parallel‐connected TEG has a much smaller internal resistance and is thus suitable for wearable/portable devices with a small load resistance. A shorter and wider TE strip generates more power. To the authors' knowledge, this is the first study that experimentally proves a downward trend of power output with increasing strip length. In addition, an industrially feasible/continuous process is proposed for large‐scale manufacture of flexible TEGs, by R2R sputtering TE materials on polymer webs, inkjet printing contacts, and segmenting using a laser. A segmented configuration is able to relieve internal strains in the device, while subjected to bending (e.g., within a wristband) to retain performance. Abstract : Herein, a flexible thin‐film thermoelectric generator (TEG) in aspects of the metal contact (the metal−semiconductor interface), the in‐line connection (in series or parallel), and the dimension of the thermoelectric strip (length and width) is optimized. Large‐scale roll‐to‐roll manufacture of flexible TEGs is also explored using an industrially feasible approach: sputtering, inkjet printing, and laser cutting.